Revisiting the Taxonomic Status of the Biomedically and Industrially Important Genus Amycolatopsis, Using a Phylogenomic Approach - Sangal, Vartul; Goodfellow, Michael; Blom, Jochen; Tan, Geok Yuan Annie; Klenk, Hans-Peter; Sutcliffe, Iain C. (Frontiers in Microbiology, 2018)
Strains belonging to the genus Amycolatopsis are well known for the production of a number of important antimicrobials and other bioactive molecules. In this study, we have sequenced the genomes of five Amycolatopsis strains including Amycolatopsis circi DSM 45561T, Amycolatopsis palatopharyngis DSM 44832T and Amycolatopsis thermalba NRRL B-24845T. The genome sequences were analyzed with 52 other publically available Amycolatopsis genomes, representing 34 species, and 12 representatives from related genera including Saccharomonospora, Saccharopolyspora, Saccharothrix, Pseudonocardia and Thermobispora. Based on the core genome phylogeny, Amycolatopsis strains were subdivided into four major clades and several singletons. The genus Amycolatopsis is homogeneous with only three strains noted to group with other genera. Amycolatopsis halophila YIM93223T is quite distinct from other Amycolatopsis strains, both phylogenetically and taxonomically, and belongs to a distinct genus. In addition, Amycolatopsis palatopharyngis DSM 44832T and Amycolatopsis marina CGMCC4 3568T grouped in a clade with Saccharomonospora strains and showed similar taxogenomic differences to this genus as well as other Amycolatopsis strains. The study found a number of strains, particularly those identified as Amycolatopsis orientalis, whose incorrect identification could be resolved by taxogenomic analyses. Similarly, some unclassified strains could be assigned with species designations. The genome sequences of some strains that were independently sequenced by different laboratories were almost identical (99–100% average nucleotide and amino acid identities) consistent with them being the same strain, and confirming the reproducibility and robustness of genomic data. These analyses further demonstrate that whole genome sequencing can reliably resolve intra- and, inter-generic structures and should be incorporated into prokaryotic systematics.